Effectiveness of T-shaped toothbrush in children: A pilot study - Mamat, Noraida; Mani, Shani Ann (Penerbit Universiti Sains Malaysia, 2018)
Dental caries and gingivitis are common oral health problems affecting schoolchildren worldwide. Effective tooth brushing in children is fundamental in preventing dental caries and gingivitis and maintaining good oral health. Children routinely present with unsatisfactory oral hygiene due to poor compliance and poor dexterity in tooth brushing. The purpose of the present study was to evaluate the effectiveness of a novel T-shaped toothbrush in plaque removal and gingival health among children and to obtain feedback regarding its use. Nineteen participants aged 8-10 years who fulfilled the criteria enrolled in this study. The children were taught the proper technique of using the new toothbrush and instructed to use it for a period of 2 weeks. The plaque scores and gingival scores were measured at baseline and after 2 weeks. They were asked to complete a questionnaire regarding the use of the toothbrush after 2 weeks. Statistical analysis was performed using t-test. There was a statistically significant (p < 0.05) reduction in mean (SD) plaque scores from baseline 1.96 (0.85) to 1.51 (0.75), after 2 weeks. Similarly, mean (SD) gingival scores reduced significantly from 0.20 (0.11) to 0.13 (0.08) over the two-week period. Overall, majority of participants (68% to 89%) gave positive feedback in all aspects regarding the use of T-shaped toothbrush, although 63.2% of them reported having difficulties to handle the T-shaped toothbrush initially. The T-shaped toothbrush can effectively improve oral hygiene in children with acceptable plaque removal and adequate gingival health in children.